Teach Your Child How to Think - De Bono, Edward (London Penguin Books, 1993)
Shows in a simple and practical way how any parent can develop the thinking skills of their children. This book gives techniques for coping with the many problems and opportunities that lie in wait for your child. It not about winning arguments, learning facts or articulation, but about constructive thinking, making the right choices and planning.
Include Appendix
Keywords: Cognition in children -- Thought and thinking -- Creative thinking--Study and teaching